Towards a Sustainable Halal Ecosystem: Regulators' Perspectives in the Era of Mandatory Halal Certification 2026 - Ismail Ismail; Andri Soemitra; Zuhrinal M. Nawawi; Azhari Akmal Tarigan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines stakeholder perspectives on the mandatory halal certification requirement for Small and Medium Enterprises (SMEs) in North Sumatra, which will take effect in 2026. The core issue explored is how this obligation presents both opportunities and challenges in enhancing the competitiveness of SMEs. The study aims to identify barriers, solutions, and cross-sector collaborations in the implementation of halal certification. This research employs a qualitative descriptive approach, utilizing in-depth interviews with informants from government bodies, academia, and SME assistance institutions. The findings indicate that halal certification contributes to increased consumer trust and strengthens SME competitiveness. However, significant challenges remain, including high certification costs, complex procedures, and a lack of awareness campaigns. Proposed innovations include simplifying certification procedures, government subsidies, and technical training and assistance. This study updates the existing literature by highlighting the role of cooperative agencies and SME assistance institutions in the halal supply chain, which has previously received limited attention. In this context, cross-sector collaboration and flexible policies are essential to overcoming the challenges faced by SMEs, ensuring inclusive access to halal certification, and enhancing global competitiveness.‎